Scripted Fantasies and Innovative Orientalisms: Media, Youth, and Ideology in the Age of the "War on Terror". (December 2017) - De Lissovoy, Noah; Ramaprasad, Venkat; Cedillo, Stacia; Cook, Courtney B.
Anxieties associated with global conflict surround youth and ideological narratives mediating these conflicts can be seen in the popular media youth consume. This investigation uses contemporary cultural-theoretical conceptualizations of ideology to analyze several important popular screen-based cultural artifacts created for youth consumption to determine how young audiences are invited into the ideoscapes and discourses of global politics in the age of the "war on terror." The analysis shows that these youth-oriented media artifacts script fundamental understandings of conflict and provide schema in which young viewers can orient themselves in relation to global Others, while also setting the matrix of intelligibility within which global politics itself becomes coherent. In addition, these popular cultural texts undertake an innovation of familiar Orientalisms, inviting young people to identify with an aggressive defense of the West and serving as an ideological support for the United States in the context of ongoing global conflicts.